Retrotrans-genomics identifies aberrant THE1B endogenous retrovirus fusion transcripts in the pathogenesis of sarcoidosis - Shunsuke Funaguma; Aritoshi Iida; Yoshihiko Saito; Jantima Tanboon; Francia Victoria De Los Reyes; Kyuto Sonehara; Yu-ichi Goto; Yukinori Okada; Shinichiro Hayashi; Ichizo Nishino (Nature Communications)
Abstract Transposon-like human element 1B (THE1B) originates from ancient retroviral sequences integrated into the primate genome approximately 50 million years ago, now accounting for at least 27,233 copies in the human genome, suggesting their extensive influence on human genomic architecture. Here we report identification of 19 THE1B fusion transcripts through short- and long-read RNA-seq analysis, 15 of which are previously unmapped, showing elevated expression in 16 individuals with sarcoid myopathy (SM), as compared to 400 controls with various other muscle diseases. Analysis of publicly available RNA-seq data indicated a correlation between the reduced expression of eight THE1B fusion transcripts and clinical improvement in individuals with cutaneous sarcoidosis receiving tofacitinib treatment. Single-cell or single-nucleus RNA-seq analyses of sarcoidosis not only confirmed these transcripts but also revealed a novel read-through transcript, SIRPB1-SIRPD, and TREM2.1, predominantly in granuloma-associated macrophages. The expression profiles of THE1B fusion transcripts in tuberculosis (TB) significantly differed from SM in single-cell RNA-seq data, suggesting that the differences between TB’s caseous granulomas and sarcoidosis’s non-caseous granulomas might be linked to disparate expression patterns of THE1B fusion transcripts. Our retrotrans-genomics approach has not only identified the genomic landscape of sarcoidosis but also provided new insights into its etiology.